2020
DOI: 10.3390/ijms21051884
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Among Circadian Rhythm, Obesity and Allergy

Abstract: The circadian clock system works not only as a cellular time-keeper but also as a coordinator for almost all physiological functions essential to maintaining human health. Therefore, disruptions or malfunctions of this system can cause many diseases and pre-symptomatic conditions. Indeed, previous studies have indicated that disrupted clock gene expression rhythm is closely related to obesity, and that allergic diseases can be regulated by controlling peripheral clocks in organs and tissues. Moreover, recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 97 publications
1
10
0
5
Order By: Relevance
“…Imbalances in meal timing, such as shift work, or situations such as skipping meals can also lead to disruptions in biological rhythms. It has been reported that skipping breakfast, which is the first meal of the day, increases the risk of obesity more than skipping lunch or dinner (Orihara et al, 2020). In fact, in a study, it was observed that weight loss was higher when participants who consumed a single 2000 kcal meal in the morning were compared with those who consumed it in the evening (Halberg et al, 1995).…”
Section: Circadian Rhythm and Obesitymentioning
confidence: 99%
“…Imbalances in meal timing, such as shift work, or situations such as skipping meals can also lead to disruptions in biological rhythms. It has been reported that skipping breakfast, which is the first meal of the day, increases the risk of obesity more than skipping lunch or dinner (Orihara et al, 2020). In fact, in a study, it was observed that weight loss was higher when participants who consumed a single 2000 kcal meal in the morning were compared with those who consumed it in the evening (Halberg et al, 1995).…”
Section: Circadian Rhythm and Obesitymentioning
confidence: 99%
“…Многие исследователи в начале нового тысячелетия стали отмечать положительную ассоциацию между наличием ожирения и клиническими проявлениями аллергии или уровнем общего IgE в сыворотке крови как маркера атопии [5,6], а также рассматривать ожирение в качестве фактора риска астмы и предиктора тяжести ее течения [7]. Одно из первых таких исследований, проведенное в США, выявило положительную корреляцию уров-ня общего IgE у детей в возрасте от 2 до 19 лет не только с индексом массы тела (ИМТ), но и с Среактивным протеином [8]. Однако результаты других работ оказались не столь однозначными [9][10][11], что могло быть связано с различиями в дизайне проведенных исследований, возрасте изучаемой популяции, с социально-экономическими характеристиками, а также с используемыми методологическими и диагностическими подходами [12].…”
Section: эпидемиологические тенденцииunclassified
“…МЕХАНИЗМОВ В настоящее время существует множество гипотез, объясняющих возможную взаимосвязь между ожирением и атопией. Важнейшая из них основана на данных об изменении работы иммунной системы человека в условиях избыточного веса, связанном преимущественно с увеличением продукции воспалительных медиаторов и формированием хронического неинфекционного воспаления [8].…”
Section: общность патогенетическихunclassified
“…While the suprachiasmatic nucleus is the master clock, many organs display a secondary clock that can, in some cases, be asynchronous due to the shift of important cues (e.g., change in feeding time can alter the stomach internal clock [ 141 ]). It has been established that circadian rhythms play an important role in many physiological processes on the ground including sleep cycle [ 142 ], gut microbiota [ 143 ], energy metabolism [ 144 ], heart rate and blood pressure [ 145 , 146 ], and that disturbances in our innate rhythm can lead to obesity [ 147 , 148 , 149 ], diabetes [ 148 ], and fertility complications [ 150 ]. Onboard the international space station (ISS) astronauts can witness 16 sunrises and sunsets every day, however, indoor lighting is used as a mitigating strategy [ 151 ] and simulates a 24-h cycle within the habitat.…”
Section: Outstanding Questionsmentioning
confidence: 99%